Combination effect of laser diode for photodynamic therapy with doxycycline on a wistar rat model of periodontitis - Suryani Dyah Astuti; Irawan Budi Utomo; Ernie Maduratna Setiawatie; Miratul Khasanah; Hery Purnobasuki; Deny Arifianto; Kartika Anggraini Alamsyah (BMC, 2021)
Abstract Background Periodontitis is a chronic inflammatory disease characterized by progressive damage on the structure of tooth-supporting tissues. The aim of the study is determining the combination photodynamic effect of diode laser 405 nm treatments and the administration of doxycycline 0.1% within 1, 3, 5, and 7 days on a Wistar rat model of periodontitis. Methods Samples were induced with Porphyromonas gingivalis ATCC33277 to allow periodontitis development and were treated with combination of doxycycline and laser diode, then statistical analysis was carried out (One-Way ANOVA test and the post-hoc Duncan test; Kruskal-Wallis test and Mann-Whitney follow-up test for non-parametric data). Samples were divided into five groups, laser exposure used was 405-nm diode laser with energy density of 8 J/cm2. The expression level of histomorphometric was calculated by measuring the number of macrophages, lymphocytes, fibroblasts and the distance between the CEJ-AV. Results The results showed that the combination treatment of doxycycline and laser exposure yielded immunomodulatory effects. The expression level of fibroblast and the distance between CEJ-AV bone showed that the combination of doxycycline and laser therapy exerted healing effect in rat models of periodontitis on day 5 and 7. Conclusion The combination of doxycycline 0.1% and diode laser therapy provides a healing effect in rats models of periodontitis.